2020
DOI: 10.21203/rs.3.rs-25605/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Hypertension on Outcomes of Adult Inpatients with COVID-19 in Wuhan, China: A Propensity Score–matching Analysis

Abstract: Background: Previous studies have shown that Coronavirus Disease 2019 (COVID-19) patients with underlying comorbidities can have worse outcomes. However, the effect of hypertension on outcomes of COVID-19 patients remains unclear.Research Question: The aim of this study was to explore the effect of hypertension on the outcomes of patients with COVID-19 by using propensity score–matching (PSM) analysis.Study Design and Methods: Participants enrolled in this study were patients with COVID-19 who had been hospita… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…In addition, 48.4% of participants with PSQI scores above 7, and 2.5% of participants reported serious sleep problems, which was higher than the results of Ding Kunxiang's study [55]. This may be due to the different time points we surveyed and changes in the social environment in rural areas [56].…”
Section: Rural Older Self-assessment Living Standard Sleep Quality An...mentioning
confidence: 90%
“…In addition, 48.4% of participants with PSQI scores above 7, and 2.5% of participants reported serious sleep problems, which was higher than the results of Ding Kunxiang's study [55]. This may be due to the different time points we surveyed and changes in the social environment in rural areas [56].…”
Section: Rural Older Self-assessment Living Standard Sleep Quality An...mentioning
confidence: 90%
“…A number of retrospective studies as well as propensity score matched and meta-analyses showed that hypertension could significantly increase severity and fatality of COVID-19 83 84 85 86 87 88 89 90 . In a retrospective observational study, COVID-19 patients with hypertension had a higher mortality rate (24.8% vs. 15.2%), a higher proportion of severe patients (63.7% vs. 42.1%), a higher proportion of patients receiving non-invasive mechanical ventilation (16.8% vs. 7.6%), and a higher proportion of patients transferred to the intensive care unit (ICU) (23.9% vs. 12.2%).…”
Section: Covid-19 Hypertension and Cardiovascular Diseasementioning
confidence: 99%
“…Adjusting for confounders, such age, gender, presence of CVD, diabetes or chronic obstructive pulmonary disease (COPD) did not affect the association 86 . A propensity-score matched analysis including COVID-19 patients from Wuhan showed that patients with hypertension had significantly higher risk of death (hazard ratio (HR) 2.679;95% CI [1.237–5.805]; P=0.012;) 87 .…”
Section: Covid-19 Hypertension and Cardiovascular Diseasementioning
confidence: 99%
“…Risk factors and comorbidities linked to worse outcomes for COVID-19 patients have been identified. These include old age 5 , chronic pulmonary disease and smoking 6 , cardiovascular disease 6 , hypertension 7 , diabetes mellitus and obesity 8 . Patients with pre-existing diabetes mellitus, depending on nations and patient cohorts, have been reported to account for patients with COVID-19 from 5-20% in China, 17% in Lombardy in Italy to 33% in the US 1-5 .…”
Section: Introductionmentioning
confidence: 99%